(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The planktonic foraminifer and calcareous nannofossil content of two Middle Miocene sections of the Tremiti Islands (Southern Adriatic Sea) have been studied. The two sections are composed of marly limestones rich in calcareous plankton which show cyclic alternations of indurated (higher carbonate content) whitish and less indurated grey or reddish beds. The two sections represent a succession with a total thickness of 38 m. Samples have been collected at a mean spacing of 10-15 cm; qualitative analyses were performed on one sample per meter but quantitative analyses were made for each sample. The abundance fluctuations of several marker species proved to be a very useful tool to correlate the two sections. The astronomical calibration of the sedimentary cycles provided absolute ages for all the recognised calcareous plankton bioevents.